Caracteriza????o molecular de doen??as raras do esqueleto - Marques, Felipe Albuquerque (2015)
Genetic diseases of the skeleton affect the genesis of skeletal system. They are caused by mutations in genes which act on the cartilage and/or growth plate. The current classification of skeletal anomalies describes more than 456 distinct phenotypes organized into 40 groups. Of this total, 360 phenotypes are associated with defects in 336 genes (thus, 90 diseases remain to have their cause elucidated). The development of high resolution techniques for genomic analysis has enabled more genetic diseases, including skeletal phenotypes, to have molecular basis clarified. This research aimed to identify genes or regions in the human genome associated with genetic diseases of the skeleton. To this end, a pipeline was developed involving experiments and data analysis. Investigation of single nucletoide variation (SNV) was carried out using whole exome sequencing (WES) and submicroscopic structural variations were analyzed by Chromossomal Microarray Analysis (CMA). Moreover, Sanger sequencing, Fluorescence in situ Hybridization, in vitro functional tests (cell culture, qRT-PCR, Western Blot, Immunofluorescence and transcriptome), Immunohistochemistry and histochemistry were employed. 14 patients with rare diseases of skeleton (Craniosynostosis, s. FATCO sindrome, Catel-Manzke-like sindrome, Nager Syndrome and Rodriguez Syndrome) were selected. Craniosynostosis: of three patients, two had their molecular diagnoses elucidated, one with mutation in FGFR3 and the other with a translocation involving chromosomes 17q and 20q. s. FATCO: it wasn't possible to identify the causative mutation for this disease. Catel-Manzke-like Syndrome: initially this patient was diagnosed as Catel-Manzke Syndrome, and there was found a mutation in EXT2. Thus, this patient was reclassified as a new syndrome recently reported as seizures-scoliosis-macrocephaly. Nager and Rodriguez Syndrome: two of four have been diagnosed with mutation in SF3B4. For these patients, the results of qRT-PCR, Western Blot and Immunofluorescence together suggested that the phenotype is caused by SF3B4 haploinsuficiency. Immunohistochemistry and Histochemistry showed the expression of SF3B4 in cartilage tissue and the disorganization of hypertrophic cells in growth plate, respectively. The transcriptome result from cartilage tissue of one patient with SF3B4 mutation showed 12 underexpressed genes involved in skeletogeneses. The combination of techniques like classical cytogenetics and molecular cytogenetics as well as sequencing and in vitro assays were effective to achieve a diagnosis. Although there was an investigative core common to all diseases, investigations were customized to each case, seeking greater efficiency in the detection of the molecular basis and cost optimization of molecular research.